2009
DOI: 10.1007/s11240-009-9659-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of the endangered plant Centaurea ultreiae: assessment of genetic stability by cytological studies, flow cytometry and RAPD analysis

Abstract: The effect of different cytokinins on multiple shoot regeneration from shoots of Centaurea ultreiae was studied. The culture system consisted of solid basal halfstrength Murashige and Skoog medium supplemented with one of four cytokinins [6-benzyladenine (BA), zeatin, kinetin, or N 6 -(2-isopentyl) adenine (2-iP)] at each of five different concentrations. The highest multiplication rate (5.52 shoots per explant) was obtained in the medium supplemented with 4.44 lM BA. Shoots were successfully rooted (91% succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 32 publications
2
45
0
1
Order By: Relevance
“…4), showing genetic stability of the micropropagated plants. Similar reports showing the genetic stability of micropropagated plants was reported in Centaurea ultreiae and Nepenthes khasiana (Mallon et al 2010;Devi et al 2013).…”
Section: Cytological Analysissupporting
confidence: 87%
“…4), showing genetic stability of the micropropagated plants. Similar reports showing the genetic stability of micropropagated plants was reported in Centaurea ultreiae and Nepenthes khasiana (Mallon et al 2010;Devi et al 2013).…”
Section: Cytological Analysissupporting
confidence: 87%
“…Flow cytometry has been widely used to detect variation in ploidy level of plants micropropagated because of relatively low cost, high yield and precision of analysis (Rahman and Rajora, 2001;Loureiro et al, 2007;Mallón et al, 2010). Brito et al (2010) found no genetic variation when two wild olives (Olea maderensis L. and O. europaea spp.…”
Section: Discussionmentioning
confidence: 99%
“…Somaclonal variation and guarantee completely genetic fidelity (Mallón et al, 2010) can´t be detected by any techique. Therefore, the adoption of different methodologies is necessary to assess genetic stability of micropropagated plants (Peredo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, special solicitude should be remunerate to protect and preserve the endemic flora that is normally found in limited areas (Fay 1992;Sarasan et al 2006). Conservation of endemic species by plant tissue culture has attracted the attention of many researchers (Mallon et al 2010;Piovan et al 2010). Lamiaceae herbs namely basil, oregano, sage, marjoram and rosemary are popular aromatic herbs.…”
Section: Introductionmentioning
confidence: 99%